Effect of ninjin'yoeito, a Kampo (traditional Japanese) medicine, on cognitive impairment and depression in patients with Alzheimer's disease: 2 years of observation. Issue 2 (27th April 2015) - Kudoh, Chiaki; Arita, Ryutaro; Honda, Mitsuru; Kishi, Taichi; Komatsu, Yasuhiro; Asou, Hiroaki; Mimura, Masaru
Abstract: Background: Only a few approved drugs are capable of alleviating the cognitive and behavioural symptoms of people living with Alzheimer's disease (AD). In recent years, however, the number of studies examining the clinical effects of herbal medicines on cognitive function in patients with AD has increased considerably. This study evaluated the long‐term effects of a traditional Japanese medicine (Kampo medicine) known as ninjin'yoeito (NYT) on cognitive impairment and mood status in patients with AD over a 2‐year period. Methods: Twenty‐three patients with mild‐to‐moderate probable AD according to the National Institute of Neurological and Communicative Disorders and Stroke and Alzheimer's Disease and Related Disorders Association criteria were included. Each participant had exhibited an insufficient response to treatment with donepezil alone before the start of the trial. Eleven patients received treatment with donepezil alone, and the remaining patients received a combined treatment of donepezil and NYT for 2 years. Patients were assessed by the Mini‐Mental State Examination and the Alzheimer's Disease Assessment Scale‐cognitive component‐Japanese version for cognitive function, and the Neuropsychiatric Inventory was used to evaluate the patients' mood status at baseline and every 6 months for 2 years. Results: The Mini‐Mental State Examination results showed no significant differences between the two groups. Significant improvements were observed on the Alzheimer's Disease Assessment Scale‐cognitive component‐Japanese version and the Neuropsychiatric Inventory depression scores of patients who received the combined therapy with donepezil and NYT (Alzheimer's Disease Assessment Scale‐cognitive component‐Japanese version, 12 months: P < 0.01, 18 months: P = 0.04, 24 months: P < 0.01; Neuropsychiatric Inventory depression, 6 months: P < 0.05, 24 months: P < 0.05). Conclusions: A 2‐year follow‐up of patients receiving donepezil and NYT treatment showed an improved cognitive outcome and alleviation of AD‐related depression.